2021
DOI: 10.1088/1755-1315/674/1/012085
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on biological aspects of the orange-spotted grouper (Epinephelus coioides) harvested in the northern coast of Aceh, Indonesia

Abstract: Considered as the least concern (LC) based on the IUCN category, the biological information of Epinephelus coioides is limited. The present study’s objective was to study some biological aspects of the orange-spotted grouper harvested in the northern coast of Aceh. The fishes were collected from June - August 2020 in several fish landing sites (TPI) and fish market located in Banda Aceh and Aceh Besar district. In total, 30 fish specimens were collected in this study. The total length (TL) of the fishes ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…In addition, the average relative weight (Wr) was greater than 100 (100.59 ± 11.28 g). The value corresponds with previous grouper studies worldwide [13,14]. Similar findings were also reported in several marine fishes surveys [4,21].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the average relative weight (Wr) was greater than 100 (100.59 ± 11.28 g). The value corresponds with previous grouper studies worldwide [13,14]. Similar findings were also reported in several marine fishes surveys [4,21].…”
Section: Resultssupporting
confidence: 92%
“…There have been limited extensive studies on length-weight relationships (LWR) and condition * Corresponding author: nurfadli@unsyiah.ac.id factors of groupers in Aceh. For example, the study on the growth pattern of the leopard coralgrouper (Plectropomus leopardus), blacksaddled coralgrouper (P. laevis), duskytail grouper (E. bleekeri), and brownmarbled grouper (Epinephelus fuscoguttatus) [12]; the golden hind grouper (Cephalopholis aurantia) [13]; the orange-spotted grouper (Epinephelus coioides) [14] and white-edged lyretail (Variola albimarginata) [15]. However, similar information is not available for Cephalopholis argus in the northern Aceh region.…”
Section: Introductionmentioning
confidence: 99%
“…The relative weight value displayed in this research corresponds with previous grouper studies. For example, Fadli et al [17] and Fadli et al [18] reported that the Wr value of the golden hind grouper (Cephalopholis aurantia) and the orange spotted grouper (E. coioides) fished in northern Aceh waters were 100.23± 7.13 and 100.08± 4.20, respectively. Comparable results were also described in several marine fishes studies.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Ramadhani et al[16] and Bulanin et al[14] found that growth pattern of groupers (Plectropomus leopardus, P. laevis, E. fuscoguttatus, and E. bleekeri) in northern Aceh and E. coeruleopunctatus harvested in the coastal waters of Padang City, respectively, displayed negative allometric pattern. In another study, Fadli et al[18] and Damora et al[19] also reported negative allometric patterns for E. coioides and white-edged lyretail (Variola albimarginata) harvested in northern Aceh. The value of biological parameters, the relationship between length and weight, and condition factor for Epinephelus areolatus, Epinephelus fasciatus, and Epinephelus merra harvested on the northern coast of Aceh…”
mentioning
confidence: 91%
See 1 more Smart Citation